A new species of Brueelia Kéler, 1936 (Phthiraptera: Ischnocera: Philopteridae) from the blue-black grassquit (Aves: Passeriformes: Emberizidae) in Brazil - Valim, Michel P.; Palma, Ricardo L. (Zootaxa, 2006)
A new species of Brueelia Kéler, 1936 is described and illustrated, based on lice collected from the blue-black grassquit, Volatinia jacarina (Linnaeus, 1766), in Brazil. This is the first species of Philopteridae recorded from this Neotropical passeriform species.